Robust Anode‐Free Sodium Metal Batteries Enabled by Artificial Sodium Formate Interface - Wang, Chaozhi; Zheng, Ying; Chen, Zhe‐Ning; Zhang, Rongrong; He, Wei; Li, Kaixuan; Yan, Sen; Cui, Jingqin; Fang, Xiaoliang; Yan, Jiawei; Xu, Gang; Peng, Dongliang; et al. (Advanced energy materials, 2023)
Sodium metal batteries (NMBs) have attracted increasing attention as next‐generation rechargeable batteries. How to improve their cycling stability and safety under limited sodium excess conditions, ideally zero sodium excess (i.e., anode‐free architecture), is highly desired yet remains challenging. Herein, it is demonstrated that sodium formate (HCOONa), one component of the solid electrolyte interphase (SEI) naturally formed on sodium metal anode, is a promising candidate for designing high‐performance artificial SEI layers, which can suppress the sodium dendrite formation and reduce the side reactions between sodium and the electrolyte. Profiting from the HCOONa interface, the Na|Na3V2(PO4)3 battery with a high mass loading of Na3V2(PO4)3 (10 mg cm−2) exhibits a superior cycling stability with an ultralow decay rate of 0.004% per cycle over 800 cycles. More impressively, a single molecular layer of HCOONa in situ formed on commercial copper current collector helps to extend the lifespan of the anode‐free Cu|Na3V2(PO4)3 battery to 400 cycles with 88.2% capacity relation, representing the longest cycle lifetime reported in anode‐free NMBs. An in situ formed HCOONa interface is proposed to protect sodium metal anodes and construct stable anode‐free sodium metal batteries. The HCOONa interface can suppress the growth of dendrites and reduce the parasitic reaction of the electrolyte, which effectively improves the capacity and cycling stability of anode‐free sodium metal batteries.